SEO centrado en el usuario: un cambio de paradigma orientado a satisfacer mejor las necesidades de las personas en el buscador de Google - Alcaraz Martínez, Rubén (Cuadernos de Documentación Multimedia, 2022)
Search engines are the main point of access to the contents of websites. SEO is the practice aimed at increasing the quantity and quality of traffic to a website through organic search results from search engines. The SEO work seeks to satisfy certain ranking factors that are considered by search engine algorithms in ordering search results. In recent years, we have seen how these algorithms have been turning towards factors and signals aimed at prioritizing those results that best satisfy the search intent behind the keyword used, also offering the best possible user experience on the landing page. After a bibliographical analysis of the factors related to the analysis of the search intent and the factors related to the improvement of the user experience from an SEO point of view in the Google search engine, we identify a set of actions and strategies that can be implemented with the aim of improving the positioning of the pages of a website.